2006
DOI: 10.1007/s10120-005-0351-6
|View full text |Cite
|
Sign up to set email alerts
|

Weekly paclitaxel as second-line chemotherapy for advanced or recurrent gastric cancer

Abstract: Weekly paclitaxel seems to be active as second-line chemotherapy against metastatic and recurrent gastric cancer. Further study is needed to confirm the efficacy and safety of weekly paclitaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 13 publications
6
95
5
Order By: Relevance
“…Neutropenia was one of the most frequently reported adverse events in both treatment arms, and the incidence in the PL ? PTX arm was within the range of that reported in other Japanese and Western trials with a similar paclitaxel dose and schedule [7,[11][12][13]. Neutropenia was commoner in the Japanese population, but this could be managed safely, as indicated by the longer median duration of therapy in the RAM ?…”
Section: Discussionsupporting
confidence: 67%
“…Neutropenia was one of the most frequently reported adverse events in both treatment arms, and the incidence in the PL ? PTX arm was within the range of that reported in other Japanese and Western trials with a similar paclitaxel dose and schedule [7,[11][12][13]. Neutropenia was commoner in the Japanese population, but this could be managed safely, as indicated by the longer median duration of therapy in the RAM ?…”
Section: Discussionsupporting
confidence: 67%
“…In previous phase II trials, weekly PAC administration was found to be active against GC with peritoneal metastasis (14,15). Moreover, it has been suggested that the regimen is feasible, safe and shows consistent activity against heavily treated GC in a second-line or further setting (12,20). neutropenia (14.9%), anemia (10%), leukopenia (4%), and anorexia (4%) were the most common grade 3/4 adverse events observed in this study, occurring less frequently than in previous reports.…”
Section: Discussionsupporting
confidence: 49%
“…Consequently, CPT-11 may be a key novel agent for the treatment of advanced GC in a second-line setting. On the other hand, the weekly administration of paclitaxel (PAC) for GC following the failure of prior chemotherapy has become standard practice in Japan, as it offers milder toxicities than a tri-weekly schedule but with equivalent activity (12,13). In previous phase II trials, it was found that PAC was active against GC with peritoneal metastasis that was refractory to regimens containing 5-FU (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The recommended optimal dose of paclitaxel in Japan was determined to be 210 mg m À2 once every 3 weeks (Yamaguchi et al, 2002). Recently, good results have been obtained with a weekly regimen of paclitaxel in patients with ovarian cancer and gastric cancer (Fennelly et al, 1997;Arai et al, 2003;Hironaka et al, 2006). The use of weekly regimens of paclitaxel, used mainly as second-line chemotherapy, has increased in Japan because of milder haematological toxicity as compared with regimens administering paclitaxel once every 3 weeks.…”
mentioning
confidence: 99%